2016
DOI: 10.1039/c6em00354k
|View full text |Cite
|
Sign up to set email alerts
|

A review of stereochemical implications in the generation of secondary organic aerosol from isoprene oxidation

Abstract: The atmospheric reactions leading to the generation of secondary organic aerosol (SOA) from the oxidation of isoprene are generally assumed to produce only racemic mixtures, but aspects of the chemical reactions suggest this may not be the case. In this review, the stereochemical outcomes of published isoprene-degradation mechanisms contributing to high amounts of SOA are evaluated. Despite evidence suggesting isoprene first-generation oxidation products do not contribute to SOA directly, this review suggests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 69 publications
(140 reference statements)
1
27
1
1
Order By: Relevance
“…Methylerythritol is more abundant (60 % of the sum of the two, as an average between two samples extracted in water and three extracted in methanol) than methylthreitol. The spectra show the occurrence of only two diastereomers among the possible four ones (González et al, 2011), indicating that the formation of methyltetrols is stereoselective, as already proposed by Cash et al (2016) on the basis of a theoretical analysis of the IEPOX chemistry, and in contrast with the conclusions of González et al (2011), claiming that methyltetrols are produced in laboratory conditions only in racemic mixtures. The two methyltetrols account for 65 % of the total 1 H-NMR signal, the rest being characterized by broad background signal with very few sharp resonances, indicating that the isoprene SOA samples are composed mainly of methyltetrols together with a significant amount of mass composed of a very complex mixture of products.…”
Section: H-nmr Fingerprints Of Non-iepox Isoprene Soacontrasting
confidence: 48%
“…Methylerythritol is more abundant (60 % of the sum of the two, as an average between two samples extracted in water and three extracted in methanol) than methylthreitol. The spectra show the occurrence of only two diastereomers among the possible four ones (González et al, 2011), indicating that the formation of methyltetrols is stereoselective, as already proposed by Cash et al (2016) on the basis of a theoretical analysis of the IEPOX chemistry, and in contrast with the conclusions of González et al (2011), claiming that methyltetrols are produced in laboratory conditions only in racemic mixtures. The two methyltetrols account for 65 % of the total 1 H-NMR signal, the rest being characterized by broad background signal with very few sharp resonances, indicating that the isoprene SOA samples are composed mainly of methyltetrols together with a significant amount of mass composed of a very complex mixture of products.…”
Section: H-nmr Fingerprints Of Non-iepox Isoprene Soacontrasting
confidence: 48%
“…Against the backdrop of the near unimaginable complexity of the atmospheric mixture of SOA precursors, the basis for our understanding of SOA formation has been primarily derived from experimental investigations of single component systems (Thornton et al, 2020;Donahue et al, 2012;Jenkin et al, 2012). A wealth of literature derived from chamber experiments on biogenic (Thornton et al, 2020;Carlton et al, 2009) and anthropogenic (Schwantes et al, 2017;Nakao et al, 2012) precursors under a range of chemical environments combined with fundamental kinetic studies (Ziemann and Atkinson, 2012;Cash et al, 2016) has enabled numerous representations of atmospheric SOA at varying levels of detail (Shrivastava et al, 2017;Charan et al, 2019). There have additionally been studies of SOA formation in source-oriented mixtures from diesel (Weitkamp et al, 2007;Nakao et al, 2011) and gasoline (Nordin et al, 2013;Platt et al, 2013) exhaust, woodburning (Tiitta et al, 2016), cooking (Reyes-Villegas et al, 2018;Kaltsonoudis et al, 2017) and from macroalgal (McFiggans et al, 2004) and plant (Joutsensaari et al, 2005;VanReken et al, 2006;Pinto et al, 2007;Mentel et al, 2009;Hao et al, 2009;Wyche et al, 2014) emissions.…”
Section: Introductionmentioning
confidence: 99%
“…However, when oligomerization based on chiral building blocks occurs, a process also relevant to secondary organic aerosol formation (Tolocka et al, 2004;Hallquist et al, 2009), changes in physicochemical properties may well occur. It has been shown that physical and chemical properties, such as melting point and water solubility, can then be determined by stereochemistry (Katsumoto et al, 2010;Baker et al, 2015;Cash et al, 2016). Thus, chirality might affect the ability of SOA formation and, consequently, influence for example the radiative forcing and cloud processing of aerosol particles.…”
Section: Introductionmentioning
confidence: 99%